Tracheal Perforation by an Oesophageal Stent - Knoop, H.; Knoop, U.; Martini, H.-C.-D.; Heining, L.; Wolf, R.; Ewig, S.; Hecker, E. (Pneumologie, 2012)
In a 63 year-old female patient with oesophageal carcinoma a tracheal perforation by an oesophageal stent was diagnosed. A first attempt of tracheal stenting was not successful due to spontaneous dislocation of the stent. Therefore, a shorter stent was chosen and correctly placed in a second session. This case report on an oesophagotracheal fistula provides a summary of this complication in advanced oesophageal cancer.